Forgery attacks on several certificateless signature schemes - Jing WANG; Zumeng LI (网络与信息安全学报)
Since Al-Riyami and Paterson proposed the novel concept of certificateless cryptography and the first certificateless signature scheme in 2003,a lot of certificateless signature schemes were proposed one after another.Recently,Tang et al proposed nine certificateless signature schemes without bilinear pairing.Although they demonstrated that their schemes were unforgeable under the assumption of elliptic curve discrete logarithmic problem,it can be found that five of their schemes could not resist the public key substitution attack,the attacker could use the user's original public key to forge a valid signature for three of these schemes.The attack methods are to demonstrate that prove five certificateless signature schemes are insecure.